Charting DENR-dependent translation reinitiation uncovers predictive uORF features and links to circadian timekeeping via Clock - Castelo-Szekely, Violeta (Nucleic Acids Res, 2019)
The non-canonical initiation factor DENR promotes translation reinitiation on mRNAs harbouring upstream open reading frames (uORFs). Moreover, DENR depletion shortens circadian period in mouse fibroblasts, suggesting involvement of uORF usage and reinitiation in clock regulation. To identify DENR-regulated translation events transcriptome-wide and, in particular, specific core clock transcripts affected by this mechanism, we have used ribosome profiling in DENR-deficient NIH3T3 cells. We uncovered 240 transcripts with altered translation rate, and used linear regression analysis to extract 5′ UTR features predictive of DENR dependence. Among core clock genes, we identified Clock as a DENR target. Using Clock 5′ UTR mutants, we mapped the specific uORF through which DENR acts to regulate CLOCK protein biosynthesis. Notably, these experiments revealed an alternative downstream start codon, likely representing the bona fide CLOCK N-terminus. Our findings provide insights into uORF-mediated translational regulation that can regulate the mammalian circadian clock and gene expression at large.